2011
DOI: 10.1063/1.3615291
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature ultraviolet detection based on InGaN Schottky photodiodes

Abstract: A thermally stable metal-insulator-semiconductor (MIS) Schottky-type photodiode with high performance based on the InGaN film is demonstrated at high temperatures up to 523 K. The reverse leakage current remains at a low level (10−7−10−8 A), while the UV responsivity is as high as 5.6 A/W at −3 V under 523 K, without observing the persistent photoconductivity. The discrimination ratio between ultraviolet (378 nm) and visible light (600 nm) is maintained to be more than 105. The temperature-dependent current-vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 11 publications
0
40
0
Order By: Relevance
“…[1][2][3][4][5][6] and MgZnO alloys, [7][8][9][10][11][12][13] have been attracting more and more attention due to their huge potential for applications (missile plume warning, flame/engine control, air/ water purification, etc.). Different structures, such as photoconductive, 3,12 p-i-n, 11,13 Schottky barrier, 2,4,5,10,11 and metal-semiconductor-metal (MSM) 1,5,7,9 were used in the fabrication of these PDs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6] and MgZnO alloys, [7][8][9][10][11][12][13] have been attracting more and more attention due to their huge potential for applications (missile plume warning, flame/engine control, air/ water purification, etc.). Different structures, such as photoconductive, 3,12 p-i-n, 11,13 Schottky barrier, 2,4,5,10,11 and metal-semiconductor-metal (MSM) 1,5,7,9 were used in the fabrication of these PDs.…”
mentioning
confidence: 99%
“…While several physical mechanisms have been proposed for the explanation of such a gain, most of the authors [1][2][3]5,[7][8][9][14][15][16] attribute the gain phenomenon to the existence of trapping states at the active layer-metal interface. In GaN-type materials, these traps are generally attributed to threading dislocations, having acceptor-like nature.…”
mentioning
confidence: 99%
“…However, there are only limited works on the electrical and structural properties of InGaN Schottky barrier diodes (SBDs). For example, Sang et al [7] investigated the thermally stable high performance InGaN metal-insulator-semiconductor (MIS) Schottky-type photodiode by using CaF 2 as an insulating layer. The temperature dependent current-voltage (I−V ) characteristics were analysed by using the thermionic-field emission (TFE) and field emission (FE) tunnelling mechanisms from room temperature to 463 K and concluded that TFE is the dominant mechanism at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Indium gallium nitride (InGaN), a ternary compound of III-nitride semiconductors, has received considerable attention due to its potential applications in optoelectronic devices [48][49][50][51]. The choice of InGaN as an active layer in high-performance optoelectronic devices is due to the advantage one gets in tuning the energy bandgap from visible to near-ultraviolet region by changing the In composition.…”
Section: Polar Ingan/gan Heterostructuresmentioning
confidence: 99%